2011
DOI: 10.1177/0300985811419529
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Molecular Analysis of 39 Spontaneous Feline Pulmonary Carcinomas

Abstract: The present study was performed to determine the morphologic change and selected molecular features of spontaneous lung tumors in cats examined at the North Carolina State University Veterinary Teaching Hospital. Thirty-nine primary lung carcinomas represented 0.69% of all feline cases admitted to the hospital. Most lung tumors were observed in aged cats (P < .0001), and no sex predilection was found (P < .4241). Persian cats with pulmonary carcinoma were overrepresented in the data set, at least 4 times more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
88
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(108 citation statements)
references
References 26 publications
14
88
2
4
Order By: Relevance
“…The lung-digit syndrome is more common in elderly cats, with a mean age of 10 to 14 years [1]. No breed or gender predisposition has been reported in felines, with the possible exception of Persian cats [5]. The present report, which describes the case of a 16-year-old Himalayan cat (a cross between the Persian and Siamese breeds), agrees with most studies suggesting that older cats are more often affected.…”
Section: Discussionsupporting
confidence: 87%
“…The lung-digit syndrome is more common in elderly cats, with a mean age of 10 to 14 years [1]. No breed or gender predisposition has been reported in felines, with the possible exception of Persian cats [5]. The present report, which describes the case of a 16-year-old Himalayan cat (a cross between the Persian and Siamese breeds), agrees with most studies suggesting that older cats are more often affected.…”
Section: Discussionsupporting
confidence: 87%
“…In cats, the incidence of lung carcinoma has increased in the last years (2,5,14). This finding may be explained by longer lifespans and an increase in the number of animal necropsies being performed and reported (2,14). This population is composed by older domestic cats, short hair, and with a mean age of 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…TTF-1 has been described as a highly specific marker in lung adenocarcinomas in human and dog (7,11). D'Costa et al, (2) showed a labeling specificity of 66.7% in feline lung tumors and it was the highest percentage when compared with other antibodies Surfactant A (SP-A) (50%), Epidermal growth factor receptor (EGFR) (20.8%) and p53 (25%), suggesting the importance of these protein as marker to support the diagnosis of pulmonary tumors in the cat. In this case, histochemical (PAS) and immunohistochemistry (CK7, CK20 and TTF-1) staining were useful for the diagnostic of pulmonary tumor and as well as their classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations